Soil preparation and NPK fertilization in the planting of five Atlantic Rainforest species in a clay extraction area - Pinheiro, Ana Paula Braido; Jardim, Adriele dos Santos; Silva, João Vitor Garcia; Fernandes, Adriano Alves; Pires, Fábio Ribeiro; Menezes, Luis Fernandes Tavares de; Schmildt, Edilson Romais; Machado, Frederico Santos (Ciência e Natura, 2020)
The occurrence of degraded areas worldwide grows each year and measures must be taken to mitigate degradation and to recover these areas. The aim of this study was to assess the effect of soil preparation and NPK levels on the growth of five native species of the Atlantic Rainforest in clay extraction area. The experimental design was randomized block in a split-split plot arrangement with four replications. Subsoiling and scarification soil preparation represented main plots. Doses of NPK 04-14-08: 0; 40; 80;160; and 320 g pit-1 represented subplots and Atlantic Rainforest native species represented sub-subplots. Absolute growth rate, stem diameter and number of leaves were evaluated, 210 days after planting. The type of soil preparation did not influence the development of the species. The best dose for Dalbergia ecastaphyllum, Inga laurina, Protium heptaphyllum and Psidium cattleyanum were 176.49, 150.18, 199.25 and 166.48 g pit-1 of NPK, respectively. Schinus terebinthifolius was highly responsive to planting fertilization, being recommended 320 g pit-1 of NPK. All species are indicated for area recovery.